2(b+2)-(6+b)=-6

Simple and best practice solution for 2(b+2)-(6+b)=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(b+2)-(6+b)=-6 equation:


Simplifying
2(b + 2) + -1(6 + b) = -6

Reorder the terms:
2(2 + b) + -1(6 + b) = -6
(2 * 2 + b * 2) + -1(6 + b) = -6
(4 + 2b) + -1(6 + b) = -6
4 + 2b + (6 * -1 + b * -1) = -6
4 + 2b + (-6 + -1b) = -6

Reorder the terms:
4 + -6 + 2b + -1b = -6

Combine like terms: 4 + -6 = -2
-2 + 2b + -1b = -6

Combine like terms: 2b + -1b = 1b
-2 + 1b = -6

Solving
-2 + 1b = -6

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 1b = -6 + 2

Combine like terms: -2 + 2 = 0
0 + 1b = -6 + 2
1b = -6 + 2

Combine like terms: -6 + 2 = -4
1b = -4

Divide each side by '1'.
b = -4

Simplifying
b = -4

See similar equations:

| 83.3x=30 | | 3(3x-4)=24 | | 3/6*8/4*2/3*6/3 | | X^2-5x-120=180 | | (6x^2+36x+28)/(x+5) | | 0.07q+0.7=0.17q-9.5 | | 9-6+u=(27-24)(2)+u | | -13+5h=12 | | 2x+14=5x+5 | | 56-(2x+13)=2(x+9)+x | | 5n+6=-7(5n-6)-6n | | (1/2x-1)^2+(1/2x-1)-72=0 | | 4x+7-6=54x+4 | | 2c^3+2c^2-4c=0 | | 9x^4+15x^3-36x^2-60x=0 | | 7.6p-3.1=42.5 | | 5.2=.04m | | 3(3x-12)=24 | | 13+1x=1 | | 2x+4-5x(x-5)=5x | | 2-6n=-5(4-n) | | -4(-8+2)=-4x-8 | | 2x^4-56x^2+150=0 | | 13x+12= | | -4c-18=-6c-8 | | 2x+10-6x=19-18x+14x-9 | | (3/5)x=15 | | -5/2=0.04m | | 5x+10=-2x+3 | | 9x-15=7x+11 | | -4=3n+2n | | 2a=5a+-15 |

Equations solver categories